Deconvolution of 40 Hz steady-state fields reveals two overlapping source activities of the human auditory cortex - Gutschalk, Alexander; Mase, Ryuzo; Roth, Rainer; Ille, Nicole; Rupp, André; Hähnel, Stefan; Picton, Terence W.; Scherg, Michael (Clinical neurophysiology, 1999)
Steady-state auditory evoked fields were recorded from 15 subjects using a whole head MEG system. Stimuli were 800 ms trains of binaural clicks with constant stimulus onset asynchrony (SOA). Seven different SOA settings (19, 21, 23, 25, 27, 29 and 31 ms) were used to give click rates near 40 Hz. Transient responses to each click were reconstructed using a new algorithm that deconvoluted the averaged responses to the different trains. Spatio-temporal multiple dipole modelling in relation to 3D MRI scans revealed two overlapping source components in both the left and right auditory cortex. The primary sources in the medial part of Heschl's gyrus exhibited a N19-P30-N40 m pattern. The secondary, weaker sources at more lateral sites on Heschl's gyrus showed a N24-P36-N46 m pattern. When applied to transient middle latency auditory evoked fields (MAEFs) recorded at SOAs of 95-135 ms, the primary sources imaged activities similar to the deconvoluted steady-state responses, but the secondary source activities were inconsistent. Linear summation of the deconvoluted source waveforms accounted for more than 96% of the steady-state variance. This indicates that the primary activity of the auditory cortex remains constant up to high stimulation rates and is not specifically enhanced around 40 Hz.